FUNDC1 is a novel mitochondrial-associated-membrane (MAM) protein required for hypoxia-induced mitochondrial fission and mitophagy. Issue 9 (1st September 2016) - Wu, Wenxian; Li, Wen; Chen, Hao; Jiang, Lei; Zhu, Runzhi; Feng, Du
ABSTRACT: Mitochondria need to be fragmented prior to engulfment by phagophores, the precursors to autophagosomes. However, how these 2 processes are finely regulated and integrated is poorly understood. We have shown that the outer mitochondrial membrane protein FUNDC1 is a novel mitochondrial-associated membrane (MAM) protein, enriched at the MAM by interacting with the ER resident protein CANX (calnexin) under hypoxia. As mitophagy proceeds, it dissociates from CANX and preferably recruits DNM1L/DRP1 to drive mitochondrial fission in response to hypoxic stress. In addition, knocking down of FUNDC1, DNM1L or CANX in hypoxic cells increases the number of elongated mitochondria and also reduces the colocalization of autophagosome and mitochondria, thus preventing mitophagy. These findings identify FUNDC1 as a molecular hub integrating mitochondrial fission and mitophagy at the MAM in response to hypoxia.